Cultural dynamics of women's lives - Bastos, Ana Cecilia de Sousa; Uriko, Kristiina; Valsiner, Jaan (Emerald Publishing Limited : Information Age Publishing, 2012)
This book explores the diverse landscapes wherein women struggle for their personal and social identities and lives, between biology and culture, destiny and choice, shared and individual worlds, tradition and modernity. Their "peripheral lives" have "central meaning" (Chaudhary, this volume) in any society - and as such are approached as a primary subject in this book, as the chapters traverse ten different countries on three continents: North America (United States); Latin America (Brazil, Chile, Colombia); Asia (India); and Europe (United Kingdom, Ireland, Portugal, Finland, Estonia).Throughout these different places, women's lives are an interesting stage for observing the interaction between biology and culture (e.g. sex vs. gender; pregnancy and childbirth vs. transition to motherhood). The focus on the cultural variability of human experience opens the door for the search of commonalities so needed in psychological theorizing. Here, this search is directed by how cultural models of womanhood (and motherhood) constrain personal experiences, especially through developmental transitions.This book is, ultimately, an opportunity to approach women's lives from the perspective of the women themselves, particularly making audible and explicit their voices and the axis of logic that structures their world. Undoubtedly, it is a valuable opportunity for women and men interested in understanding and constructing human experience inside better worlds.
Keywords: Women -- Cross-cultural studies.; Women -- Social conditions -- Cross-cultural studies.; Sex role -- Cross-cultural studies.; Women -- Identity -- Cross-cultural studies.; Social Science -- Women's Studies.; Gender studies: women and girls.; elektronické knihy; electronic books